Editor's Choice – Systematic Review and Meta-Analysis of Very Urgent Carotid Intervention for Symptomatic Carotid Disease. (November 2018) - Milgrom, David; Hajibandeh, Shahin; Hajibandeh, Shahab; Antoniou, Stavros A.; Torella, Francesco; Antoniou, George A.
Abstract : Background: The optimum timing of carotid intervention for symptomatic carotid stenosis remains unclear. The objective was to investigate outcomes of very urgent (< 48 h from neurological event) in comparison to urgent (≥ 48 h from neurological event) carotid intervention for symptomatic carotid disease. Methods: A systematic literature review was carried out of randomised control trials (RCTs) and observational studies reporting peri-procedural outcomes of carotid intervention in relation to the length of time since the neurological event (PROSPERO registration number: CRD 42017075766). Ipsilateral stroke and death were defined as the primary outcome endpoints. Transient ischaemic attack (TIA) and myocardial infarction (MI) were secondary outcome parameters. Comparative outcomes were calculated and reported as dichotomous outcome measures using the odds ratio (OR) and associated 95% confidence interval (CI) for very urgent (< 48 h since neurological event) versus urgent (≥ 48 h) intervention. The combined overall effect size was calculated using a random effects model. Results: Twelve observational studies and one RCT representing 5751 interventions, 5385 carotid endarterectomies (CEAs) and 366 carotid artery stenting (CAS) procedures, were included in quantitative synthesis. Very urgent carotid intervention was associated with increased risk of stroke within 30 days of treatment compared with urgent carotid intervention (OR 2.19, 95% CI 1.46–3.26, p  < .001). No significant difference was found in mortality (OR 1.55, 95% CI 0.81–2.96, p  = .19), TIA (OR 1.33, 95% CI 0.55–3.19, p  = .52) or MI (OR 1.33, 95% CI 0.41–4.33, p  = .64). Conclusions: Very urgent carotid intervention was found to be associated with increased risk of stroke.